Respuesta :
I'll take a stab at what I think is the most interesting problem in the attachment.
[tex]\dfrac{\mathrm dy}{\mathrm dx}=\dfrac{y+x-2}{y-x-4}[/tex]
Substitute [tex]y=s-m[/tex] and [tex]x=t-n[/tex], so that [tex]\mathrm dy=\mathrm ds[/tex] and [tex]\mathrm dx=\mathrm dt[/tex]. Then the ODE becomes
[tex]\dfrac{\mathrm ds}{\mathrm dt}=\dfrac{s-m+t-n-2}{s-m-(t-n)-4}=\dfrac{s+t-m-n-2}{s-t-m+n-4}[/tex]
We would like to have this be a homogeneous equation, which is to say, given
[tex]\dfrac{\mathrm ds}{\mathrm dt}=f(t,s)[/tex]
there is some [tex]\alpha[/tex] for which [tex]f(kt,ks)=k^\alpha f(t,s)[/tex]. In order for this to be true, we require that the constant terms in the numerator and denominator vanish. That is,
[tex]\begin{cases}-m-n-2=0\\-m+n-4=0\end{cases}[/tex]
which is easy to solve; you'd find that [tex]m=-3[/tex] and [tex]n=1[/tex]. Now, the ODE is
[tex]\dfrac{\mathrm ds}{\mathrm dt}=\dfrac{s+t}{s-t}[/tex]
Substitute [tex]s=tu[/tex], so that [tex]\dfrac{\mathrm ds}{\mathrm dt}=u+t\dfrac{\mathrm du}{\mathrm dt}[/tex], and the ODE is
[tex]u+t\dfrac{\mathrm du}{\mathrm dt}=\dfrac{tu+t}{tu-t}=\dfrac{u+1}{u-1}[/tex]
[tex]t\dfrac{\mathrm du}{\mathrm dt}=\dfrac{u+1-u(u-1)}{u-1}[/tex]
[tex]t\dfrac{\mathrm du}{\mathrm dt}=\dfrac{1+2u-u^2}{u-1}[/tex]
which is separable. You have
[tex]\dfrac{u-1}{1+2u-u^2}\,\mathrm du=\dfrac{\mathrm dt}t[/tex]
and integrating both sides is easy. Substituting [tex]v=1+2u-u^2[/tex], so that [tex]\mathrm dv=(-2u+2)\,\mathrm du[/tex], you have
[tex]\displaystyle-\frac12\int\dfrac{\mathrm dv}v\,\mathrm du=\int\dfrac{\mathrm dt}t[/tex]
[tex]-\dfrac12\ln|v|=\ln|t|+C[/tex]
[tex]-\dfrac12\ln|1+2u-u^2|=\ln|t|+C[/tex]
[tex]-\dfrac12\ln\left|1+\dfrac{2s}t-\dfrac{s^2}{t^2}\right|=\ln|t|+C[/tex]
[tex]-\dfrac12\ln\left|1+\dfrac{2(y-3)}{x+1}-\dfrac{(y-3)^2}{(x+1)^2}\right|=\ln|x+1|+C[/tex]
[tex]\dfrac{\mathrm dy}{\mathrm dx}=\dfrac{y+x-2}{y-x-4}[/tex]
Substitute [tex]y=s-m[/tex] and [tex]x=t-n[/tex], so that [tex]\mathrm dy=\mathrm ds[/tex] and [tex]\mathrm dx=\mathrm dt[/tex]. Then the ODE becomes
[tex]\dfrac{\mathrm ds}{\mathrm dt}=\dfrac{s-m+t-n-2}{s-m-(t-n)-4}=\dfrac{s+t-m-n-2}{s-t-m+n-4}[/tex]
We would like to have this be a homogeneous equation, which is to say, given
[tex]\dfrac{\mathrm ds}{\mathrm dt}=f(t,s)[/tex]
there is some [tex]\alpha[/tex] for which [tex]f(kt,ks)=k^\alpha f(t,s)[/tex]. In order for this to be true, we require that the constant terms in the numerator and denominator vanish. That is,
[tex]\begin{cases}-m-n-2=0\\-m+n-4=0\end{cases}[/tex]
which is easy to solve; you'd find that [tex]m=-3[/tex] and [tex]n=1[/tex]. Now, the ODE is
[tex]\dfrac{\mathrm ds}{\mathrm dt}=\dfrac{s+t}{s-t}[/tex]
Substitute [tex]s=tu[/tex], so that [tex]\dfrac{\mathrm ds}{\mathrm dt}=u+t\dfrac{\mathrm du}{\mathrm dt}[/tex], and the ODE is
[tex]u+t\dfrac{\mathrm du}{\mathrm dt}=\dfrac{tu+t}{tu-t}=\dfrac{u+1}{u-1}[/tex]
[tex]t\dfrac{\mathrm du}{\mathrm dt}=\dfrac{u+1-u(u-1)}{u-1}[/tex]
[tex]t\dfrac{\mathrm du}{\mathrm dt}=\dfrac{1+2u-u^2}{u-1}[/tex]
which is separable. You have
[tex]\dfrac{u-1}{1+2u-u^2}\,\mathrm du=\dfrac{\mathrm dt}t[/tex]
and integrating both sides is easy. Substituting [tex]v=1+2u-u^2[/tex], so that [tex]\mathrm dv=(-2u+2)\,\mathrm du[/tex], you have
[tex]\displaystyle-\frac12\int\dfrac{\mathrm dv}v\,\mathrm du=\int\dfrac{\mathrm dt}t[/tex]
[tex]-\dfrac12\ln|v|=\ln|t|+C[/tex]
[tex]-\dfrac12\ln|1+2u-u^2|=\ln|t|+C[/tex]
[tex]-\dfrac12\ln\left|1+\dfrac{2s}t-\dfrac{s^2}{t^2}\right|=\ln|t|+C[/tex]
[tex]-\dfrac12\ln\left|1+\dfrac{2(y-3)}{x+1}-\dfrac{(y-3)^2}{(x+1)^2}\right|=\ln|x+1|+C[/tex]